2024
DOI: 10.3390/foods13081257
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Profiling of Spirulina Food Supplements

Aikaterina Paraskevopoulou,
Triantafyllos Kaloudis,
Anastasia Hiskia
et al.

Abstract: Spirulina, a cyanobacterium widely used as a food supplement due to its high nutrient value, contains volatile organic compounds (VOCs). It is crucial to assess the presence of VOCs in commercial spirulina products, as they could influence sensory quality, various processes, and technological aspects. In this study, the volatile profiles of seventeen commercial spirulina food supplements were determined using headspace solid-phase microextraction (HS-SPME), coupled with gas chromatography-mass spectrometry (GC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 73 publications
4
3
0
Order By: Relevance
“…The results are presented in Table S1, which includes all identified analytes along with the total ion chromatogram (TIC) area of the individual chromatographic peaks. The chemical classes of the detected VOCs mainly included hydrocarbons, ketones, aldehydes, alcohols, pyrazines, furans, esters, and organic acids, which is comparable to the results of similar studies found in the literature [25,42]. Figure 1 shows the formation pathways of the main VOCs in Spirulina.…”
Section: Hs-spme-gc-ms Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…The results are presented in Table S1, which includes all identified analytes along with the total ion chromatogram (TIC) area of the individual chromatographic peaks. The chemical classes of the detected VOCs mainly included hydrocarbons, ketones, aldehydes, alcohols, pyrazines, furans, esters, and organic acids, which is comparable to the results of similar studies found in the literature [25,42]. Figure 1 shows the formation pathways of the main VOCs in Spirulina.…”
Section: Hs-spme-gc-ms Resultssupporting
confidence: 87%
“…The major aldehyde detected in the SP samples was hexanal, a volatile compound known for its characteristic grassy odor. This observation is in line with previous studies regarding SP [25,42,47] and other microalgae species [50]. Among the fresh samples, those subjected to air-drying exhibited higher levels of hexanal, indicating heightened oxidative stress on the lipids due to increased air contact.…”
Section: Lipid-derived Vocssupporting
confidence: 91%
See 3 more Smart Citations